A Study of Uncertainty and Probability in Transportation Problem - Mr. Jaydeep A. Pandya; Dr. M. M. Trivedi (Utilitas Mathematica, 2024)
The transportation problem is a special class of problem. Cost is one of the affected factors in transportation. Determine the value of transportation cost, it is solved by using different methods like the North-West Corner Method, Least Cost Method,Row (Column) Minima Method, Vogel Approximation Method, etc. but these methods cannot say about the probability. Our aim is to analyze probability in various methods of transportation and each movement in transportation is taken as an event and understand the probability dimension in these methods. Uncertainty comes from a certainty situation. Because on the other side of certainty, there should be reflected uncertainty. In this paper, we also discuss the parameter of uncertainty in various methods of transportation problems using case study. The derived results in the paper is use to establish a concreate transportation system on basis of minimize the transportation cost and allocation.